2002
DOI: 10.1016/s0960-9822(01)00650-9
|View full text |Cite
|
Sign up to set email alerts
|

Directed Proteomic Analysis of the Human Nucleolus

Abstract: This extensive proteomic analysis shows that nucleoli have a surprisingly large protein complexity. The many novel factors and separate classes of proteins identified support the view that the nucleolus may perform additional functions beyond its known role in ribosome subunit biogenesis. The data also show that the protein composition of nucleoli is not static and can alter significantly in response to the metabolic state of the cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
804
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 901 publications
(841 citation statements)
references
References 63 publications
35
804
0
2
Order By: Relevance
“…Lysates were homogenized by passing through a 22G needle. Nucleoplasmic and nucleolar fractions were prepared according to a previously published protocol (Andersen et al 2002). Protein concentration was determined using the bicinchonic acid assay.…”
Section: Cell Lysate Preparation and Western Blot Analysismentioning
confidence: 99%
“…Lysates were homogenized by passing through a 22G needle. Nucleoplasmic and nucleolar fractions were prepared according to a previously published protocol (Andersen et al 2002). Protein concentration was determined using the bicinchonic acid assay.…”
Section: Cell Lysate Preparation and Western Blot Analysismentioning
confidence: 99%
“…The N-terminal and C-terminal extensions of DDX15 seem to play a role in the subcellular localization of DDX15+ Using the anti-hPrp43/DDX15 rabbit serum, we showed that endogenous DDX15 localizes to nuclear speckles and, surprisingly, to nucleoli of HEp-2 cells (Fig+ 7)+ The subcellular localization of DDX15 to nuclear speckles and colocalization with the splicing factor U2B0 and the Sm-proteins are in agreement with the fact that the yeast ortholog Prp43 has been reported to be involved in spliceosome disassembly (Arenas & Abelson, 1997)+ Moreover, recently it was reported by Martin et al+ (2002) that Prp43 represents an essential RNA-dependent ATPase required for the release of the excised lariat-intron from the spliceosome+ The observation that DDX15 also accumulates in nucleoli suggests that, besides functioning in splicing, DDX15 is also involved in other processes (see below)+ Data from the literature on the localization of DDX15 and its homologs is very limited+ The nucleolar accumulation of DDX15 was recently corroborated by the proteomic analysis of purified human nucleoli, in which DDX15 was identified as a nucleolar protein (Andersen et al+, 2002)+ Whereas several DExD-box RNA helicases were identified, no other members of the DExH-box RNA helicase family were identified in this analysis of nucleolar proteins (Andersen et al+, 2002)+ Imamura et al+ (1997) reported that a GFP-tagged version of DBP1 localized to the nucleus of HeLa cells+ However, they did not observe the nuclear speckles and nucleolar accumulation we report in this article+ The mouse ortholog of DDX15, mDEAH9, was shown to localize to nuclear speckles, but was not observed in the nucleoli (Gee et al+, 1997)+ The discrepancies between our results and the results obtained with DBP1 and mDEAH9 might be explained by sequence differences between the three proteins+ First, the sequence of DBP1 contains a frameshift, resulting in an alternative C-terminal end in comparison with DDX15; second, whereas the murine and human proteins are almost identical over the whole protein sequence, mDEAH9 does have a shorter C-terminal part compared to DDX15 (see Fig+ 2)+ Based on these observations we suggest that the C-terminal part is important for the subnuclear localization of DDX15+ This is corroborated by the results from the deletion analysis of DDX15+ In agreement with the nuclear localization of DDX15, we identified a region required for its entry into the nucleus between amino acids 63 and 153 (see Fig+ 10)+ A deletion of amino acids 690 to 795 abolished its association with nuclear speckles, substantiating the importance of this region for its subnuclear localization+ Other DExD/H family members, like hPrp16 and HRH1, also have been reported to accumulate in speckles+ The localization of hPrp16 and HRH1 to nuclear speckles is mediated by their RS domains (Ohno & Shimura, 1996;Ortlepp et al+, 1998), which is not discernable in the DDX15 sequence+ Detailed analysis of the region spanning amino acids 690 to 795 is therefore needed to identify the amino acids involved in the targeting of DDX15 to nuclear speckles+ The nucleolar accumulation of DDX15 appeared to require two, spatially separated regions of the protein (Fig+ 10)+ Deletion of amino acids 1 to 62 in the N-terminal part abolished nucleolar accumulation, whereas the association with nuclear speckles remained unaffected+ The sequence of this region is characterized by the presence of a stretch of alternating basic and acidic residues between amino acids 25 and 60+ This repeat can be subdivided into two parts based FIGURE 10. S...…”
Section: Subcellular Localization Of Ddx15mentioning
confidence: 99%
“…What is also evident is that the nucleolus is not a static subnuclear structure but responds to a great variety of cellular stresses. DNA damage induced by ionizing radiation, UV or chemotherapeutic drugs, inhibition of RNA Pol I transcription by nutrient starvation or Actinomycin D (ActD), proteasome inhibition and viral infection, can all change nucleolar structure and alter the nucleolar proteome 18,19,20,21,22,23 .…”
Section: Introductionmentioning
confidence: 99%